Baby angels - Cowen-Fletcher, Jane. (Cambridge, Mass. : Candlewick Press, 1996)
Baby begins her day surrounded by angels who keep her out of trouble and make sure that her parents keep her close by when she tries to wander off.
Keywords: Infants -- Fiction; Angels -- Fiction; Stories in rhyme